ON THE STRATEGIC APPROACH IN ECONOMIC DEVELOPMENT OF ENTERPRISES - Malvina Gyulnezerova (Вестник Северо-Кавказского федерального университета)
The article is devoted the problem of determination and selection of development strategies of modern enterprises operating in an unstable economic development. The author justifies the relevance of strategic planning in the economic development of the enterprises, which emphasizes the role of strategy. Described approaches to the typology of economic development strategies of enterprises and describes their basic features.